Magnetic composites Fe3O4 bаsed for the purification of polluted water - Kotsyubynsky, Andrew; Lynnyk, Diana; Hrytsuliak, Halyna; Liaskovska, Mariia; Kotsyubynska, Yulia; Hrytsuliak, Vitalii; Stanetskyi, Oleksandr (Physics and Chemistry of Solid State, 2025)
Fe₃O₄ magnetic nanocomposite were synthesized from different techniques: Fe₃O₄ nanoparticles were synthesized by co- precipitation of salts in a carbon matrix (biochar, activated carbon) with the formation of Fe₃O₄/BC and Fe₃O₄/AC nanocomposites; and co-precipitation of FeCl₂/FeCl₃ with oleic acid, with formation of OL/Fe3О4 nanocomposite. Characterization techniques including XRD confirmed the spinel structure of composite matrix, with crystallite size around 20 nm. X-ray fluorescence analysis shows the presence of iron and oxygen elements, as well as impurity elements present in oleic acid and biomass carbon, respectively. The adsorption properties of all samples investigated for methylene blue (MB) dye removal. Adsorption tests were conducted at room temperature with magnetic separation of the spent adsorbent and photometric control at 665 nm. It found that magnetic composites effectively remove the dye, with AC/Fe₃O₄ achieving up to 96.6% removal at a concentration of MB 10⁻⁵ g/L.